2018
DOI: 10.4102/ajlm.v7i1.690
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost diagnostic test for susceptible and drug-resistant tuberculosis in rural Malawi

Abstract: BackgroundRural settings where molecular tuberculosis diagnostics are not currently available need easy-to-use tests that do not require additional processing or equipment. While acid-fast bacilli (AFB) smear is the most common and often only tuberculosis diagnosis test performed in rural settings, it is labour intensive, has less-than-ideal sensitivity, and cannot assess tuberculosis drug susceptibility patterns.ObjectiveThe objective of this study was to determine the feasibility of a multidrug-resistant (MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…tb isolates with determination of susceptibility was 13 days for TB-CX, compared to a median turnaround time to growth of 28 days for LJ culture, with an additional 22 days for DST results (total median of 50 days). The median TAT for TB-CX in this study was comparable to previously reported values of 10 to 13 days [5, 12, 13, 22]. Interestingly, the fastest growth was observed with two sputum samples on day 5 of incubation and results for 85% of 73 TB-CX culture-positive sputa were available within 15 days.…”
Section: Discussionsupporting
confidence: 88%
“…tb isolates with determination of susceptibility was 13 days for TB-CX, compared to a median turnaround time to growth of 28 days for LJ culture, with an additional 22 days for DST results (total median of 50 days). The median TAT for TB-CX in this study was comparable to previously reported values of 10 to 13 days [5, 12, 13, 22]. Interestingly, the fastest growth was observed with two sputum samples on day 5 of incubation and results for 85% of 73 TB-CX culture-positive sputa were available within 15 days.…”
Section: Discussionsupporting
confidence: 88%
“…This indicator causes a colour change in the medium when bacteria grow, making positive results apparent by examination with the naked eye (Lee et al, 2006;Shibabawa et al, 2019). Four TB-CX petri-plate quadrants are inoculated concurrently to test for TB and also provide concurrent DST (Robledo et al, 2008;Tovar et al, 2010;IFHAD, 2011;Toit et al, 2012;Zhang et al, 2018;Mekonnen et al, 2019;Shibabawa et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…But still others will be extensions of tried and true technologies that may not require new skills and infrastructure. For example, Zhang et al 8 (this issue) described the results of field testing a simple thin layer agar culture-based method that can detect drug-resistant tuberculosis in under 2 weeks using chromogenic plates that can be cultured in remote or resource-limited settings. While not as fast, they found it to be almost as accurate as Xpert ® MTB/RIF testing and much cheaper.…”
Section: Building Resources To Meet Evolving Laboratory Medicine Chalmentioning
confidence: 99%
“…Both the Zhang 8 and Zhou 7 articles showcase techniques that have already been deployed in other parts of the world but had not previously been piloted in African healthcare settings. In the end, an evidence-based selected suite of essential phenotypic and genotypic tests, including sequence-based ones, must be available to all patients and the more rapidly we can assess test utility in local settings, the sooner African patients will have access to faster and more precise diagnoses.…”
Section: Building Resources To Meet Evolving Laboratory Medicine Chalmentioning
confidence: 99%